2018
DOI: 10.1051/0004-6361/201832711
|View full text |Cite
|
Sign up to set email alerts
|

Three dynamically distinct stellar populations in the halo of M49

Abstract: Context. M49 (NGC 4472) is the dominant galaxy in subcluster B of the Virgo Cluster, and a benchmark for studying the build-up of the extended halos of brightest group galaxies in the outskirts of galaxy clusters. Aims. We investigate the kinematics in the outer halo of M49, look for substructures, and describe the transition to the surrounding intra-group light. Methods. As kinematic tracers we use planetary nebulae (PNe), combining kinematics from the extended Planetary Nebula Spectrograph (PN.S) early-type … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 38 publications
(62 citation statements)
references
References 89 publications
(97 reference statements)
4
57
1
Order By: Relevance
“…The second component, whether an additional component of the extended halo or in the form of diffuse IGL, is corroborated by the flattening of the stellar SB profile observed by Watkins et al (2014). Such a flattening of the PN number density profile was also observed in the outer regions of other ETGs at the centres of groups and clusters of galaxies, such as M 87 in the Virgo cluster (Longobardi et al 2013(Longobardi et al , 2015b(Longobardi et al , 2018 and M49 in the Virgo subcluster B (Hartke et al 2017(Hartke et al , 2018. It was attributed to intracluster light (ICL) or IGL with a distinct α-parameter value and spatial density distribution from the main halos of the galaxies.…”
Section: Two-component Photometric Models For the Extended Halo Of M 105mentioning
confidence: 62%
See 1 more Smart Citation
“…The second component, whether an additional component of the extended halo or in the form of diffuse IGL, is corroborated by the flattening of the stellar SB profile observed by Watkins et al (2014). Such a flattening of the PN number density profile was also observed in the outer regions of other ETGs at the centres of groups and clusters of galaxies, such as M 87 in the Virgo cluster (Longobardi et al 2013(Longobardi et al , 2015b(Longobardi et al , 2018 and M49 in the Virgo subcluster B (Hartke et al 2017(Hartke et al , 2018. It was attributed to intracluster light (ICL) or IGL with a distinct α-parameter value and spatial density distribution from the main halos of the galaxies.…”
Section: Two-component Photometric Models For the Extended Halo Of M 105mentioning
confidence: 62%
“…In order to explain the excess of PNe in the outer halos of early-type galaxies such as M 49 and M 87 in the Virgo cluster, Hartke et al (2017Hartke et al ( , 2018 and Longobardi et al (2015bLongobardi et al ( , 2018 invoked the presence of an accreted MP population at large radii with a higher α-parameter value than that of the stellar popu-lation at the inner regions of these galaxies. In addition to the higher α-parameter value, further evidence for the presence of these MP stellar populations in the outer regions of M 49 and M 87 came from a change in PNLF slope at large radii, the gradients towards bluer colours, and from the kinematics of the PNe.…”
Section: Constraints From Resolved Stellar Populationsmentioning
confidence: 99%
“…Hartke et al (2017) also found that α-parameter values for the intra-group light of M 49 is three times larger than that of its halo. Hartke et al (2018) later confirmed that the halo PNe and intra-group light PNe were kinematically different, and correspond to two separate parent stellar populations. We can thus infer that the larger α-parameter value of the bluer halo of M 31 may indicate that the stellar population of the inner halo is different from that of the disc.…”
Section: Three-component Photometric Model For M 31mentioning
confidence: 69%
“…It is seen to be correlated with the star formation history of the parent stellar population, with steeper slopes associated with older stellar populations and conversely flatter slopes with younger populations (Ciardullo et al 2004;Ciardullo 2010;Longobardi et al 2013;Hartke et al 2017). The changes in the PNLF slope can result from the superposition of multiple stellar populations, which can then be disentangled using the PNe kinematics (Longobardi et al 2015;Hartke et al 2018). The PNLF has also been shown to display a dip for some galaxies.…”
Section: Introductionmentioning
confidence: 95%
“…M87 is (in projection) near the X-ray gas emission peak (e.g., Kellogg et al 1971) which is a good tracer for the potential minimum of the cluster. Moreover, the rising velocity dispersion profile of the surrounding planetary nebulae is steeper for M87 (Longobardi et al 2018) than for M49 (Hartke et al 2018), showing that intracluster planetary nebulae are more centered on M87 than on M49. The velocity dispersion profile of the globular clusters rises towards the outskirts of M87 (Côté et al 2001) but it falls towards the outskirts of M49 (Sharples et al 1998), showing that also the intracluster globular clusters are more centered on M87.…”
Section: Introductionmentioning
confidence: 94%